A Journey to Imja Lake - Colom, Anna (United Kingdom, 2010)
The documentary tells the story of the Sherpa people in the Everest region of Nepal, who are already experiencing the effects of climate change in the Himalayas: from the changes on the mountains, their spiritual gods, to the impact on food production. On our journey to Imja Lake, we witness how the increase of temperature in the region is affecting the livelihoods of the Sherpa people and other minority groups in the area. The melting of the glaciers also poses a huge threat for the millions who depend on water from the seven main Asian rivers originating in the Himalayas.
Verzio Film Festival Submission
Keywords: Documentary films